Event-related potentials support a dual process account of the Embedded Chinese Character Task. (December 2018) - Yin, Yue; Yu, Tingting; Wang, Shu; Zhou, Shujin; Tang, Xiaochen; Stupple, Edward J.N.; Luo, Junlong
Abstract: Tests of the principles of dual process theory are typically conducted in the reasoning and judgement/decision-making literature. The present study explores dual process explanations with a new paradigm – the Embedded Chinese Character Task (ECCT). The beauty of this task is that it allows the contrast of automatic and deliberate processes without the potential for conflict. We used event-related potentials (ERPs) and behavioral measures to investigate the time course of automatic (Type 1) and deliberative (Type 2) processes on the ECCT. Thus we explored whether there were differences in processing speed in neural activation. The ECCT requires the extraction of one Chinese character from another, which requires either an automatic strategy reliant on knowledge of Chinese character formation and meaning (based on the radical ), or a deliberative strategy using the shape of the components of the character (based on the stroke ). Participants judged whether character elements were included or excluded in test characters. Faster response time were observed when judging 'inclusion relations' on automatic problems supporting the proposal that they required a Type 1 process. In line with the behavioral results, the hypothesized faster automatic process showed the rapid differentiation of N2 and P3b components between inclusion and exclusion responses, while no difference was shown for deliberative problems. Thus, neural differences in processing were shown between automatic and deliberate problems, and automatic processing was faster than deliberate processing. Highlights: Embedded Chinese character task was introduced to dual-process theory. Results showed difference when people use automatic and deliberate strategies. Significant N2 and P3b were elicited in automatic tasks. Only N2 were yielded in deliberate tasks.